PENGARUH PEMBERIAN PROBIOTIK RABAL PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN LELE DUMBO (Clarias gariepinus) - Suparman Suparman; Andi Masriah; Nurilmi Achmad (Jurnal Perikanan Unram, 2024)
Dumbo catfish (C. gariepinus) is a fish as a source of animal protein that has developed as a commodity for fisheries cultivation. Catfish cultivation technology continues to develop and has a significant effect on the efficiency of catfish cultivation and is supported by the availability of a wide market. Feed is one of the important elements in cultivation activities as one of the keys to supporting the growth and survival of cultivated fish. Providing rabal probiotics in artificial feed is one alternative to produce feed that is easily digested so that it can increase growth. This research was conducted in Mbawa Village, Donggo District, Bima Regency, West Nusa Tenggara Province, this research is an experimental study using a Completely Randomized Design (CRD) and consists of 4 treatments and 3 replications, the treatments are K (control / without giving Rabal probiotics), 8 ml / 100 grams, 10 ml / 100 grams, and 12 ml / 100 grams of feed. The parameters observed were absolute growth, specific growth, catfish survival, and water quality. The data obtained were analyzed for variety, regression using the SPSS application and analyzed descriptively. Based on the results of the analysis of variance from this study, it shows that the administration of rabal probiotics through feed produces survival, specific growth rate and absolute growth that have no significant effect (p>0.05), but based on the results of the linear regression analysis, it can be seen that the administration of rabal probiotics in feed has an effect on the survival of catfish. The highest survival value was found in the treatment of 12 mL/100 grams of feed, which was 64.10% and the lowest in the control, which was 53.84%.